Financial Behavior of Generation Z Customers Regarding Mobile Banking Satisfaction - Pandit, Mukesh Kumar; Raut, Babbar Jung; Pandey, Babita; Gautam, Saurika; Dahal, Anjila; Aryal, Savyata; Bajracharya, Rajan Bilas (International Journal of Atharva, 2025)
This study investigates the impact of financial behavior on mobile banking satisfaction among Generation Z customers. As digital financial services continue to expand, understanding the key behavioral factors influencing satisfaction becomes essential, particularly among tech-savvy youth who are rapidly adopting mobile banking platforms. The study adopts a positivist research philosophy and applies a deductive approach using a quantitative research design. A structured questionnaire was administered to a sample of 178 college students, selected through convenience sampling, to collect primary data on variables including saving behavior, perceived security, network availability, and social influence. Descriptive statistics such as frequency, mean, and standard deviation were used to analyze demographic and behavioral trends, while correlation and regression analyses were applied to determine relationships and predictive strength among variables. The findings reveal that perceived security has the strongest positive influence on mobile banking satisfaction, followed by network availability and saving behavior, all showing statistically significant relationships. In contrast, social influence did not significantly impact satisfaction levels. These results suggest that Gen Z users value secure, accessible, and practical banking experiences over peer-driven motivations. The study recommends that banks and fintech platforms prioritize security features, reliable infrastructure, and personal finance tools to enhance satisfaction among young digital consumers.